COVID-19 booster prioritization in the West Bank: a survey experiment among Bedouins, refugees, and the majority group - Carol, Sarah; Amro, Ahmad (Frontiers in Public Health, 2023)
Introduction Our main aim is to understand to what extent Bedouins, internally displaced Palestinians (refugees) and majority-group members (non-refugees, non-Bedouins, settled) in the West Bank prioritize COVID-19 booster shots for their own group over other groups. Methods We conducted a survey experiment (face-to-face) among 678 Palestinians living in the West Bank. Participants randomly received a description of an older man (Bedouin, refugee, settled) and were asked to indicate to what extent this person should be prioritized for the booster shot. Respondents belonging to a minority saw the profile of an in-group member or a majority-group member, whereas majority-group members would see the profile of an in-group or one out-group member (Bedouin, Palestinian refugee). Results We found slightly higher in-group preferences for Palestinian refugees when it came to vaccination, whereas majority-group members were less inclined to support a prioritization of Palestinian refugees but equally prioritized their group and Bedouins. For Bedouins, we did not find strong in-group preferences. Discussion Our study reveals the salience of group boundaries during the COVID-19 pandemic with potentially adverse effects on the health care of minorities.